2001
DOI: 10.1159/000050462
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Changes of Sensitization to Farming-Related Antigens among Young Farmers

Abstract: Background: We have shown previously that the prevalence of allergic sensitization in Tyrolean farming students is high, with a clear relationship to occupational exposure. Objectives: It was the aim of this investigation to assess longitudinal changes in sensitization and a possible impact on lung function. Methods: Of the 147 farming students in the original cohort, we could re-examine 42 after a mean interval of 4.0 years. All individuals completed a questionnaire and had spirometry, skin prick tests, total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…Conversely, endotoxin is thought to reduce the risk of allergic sensitisation by inducing a shift from allergic T-helper cell (Th) type 2 responses to Th1-dominated responses, through stimulation of the innate immune system and regulatory T-cells [28]. The results of the present study suggest that inhaled endotoxin may exert such immune-modulating effects beyond childhood, and similar conclusions were previously derived from a longitudinal study showing that young adult dairy farmers may lose allergic sensitisation over time, especially to grass pollen [29].…”
Section: Discussionsupporting
confidence: 83%
“…Conversely, endotoxin is thought to reduce the risk of allergic sensitisation by inducing a shift from allergic T-helper cell (Th) type 2 responses to Th1-dominated responses, through stimulation of the innate immune system and regulatory T-cells [28]. The results of the present study suggest that inhaled endotoxin may exert such immune-modulating effects beyond childhood, and similar conclusions were previously derived from a longitudinal study showing that young adult dairy farmers may lose allergic sensitisation over time, especially to grass pollen [29].…”
Section: Discussionsupporting
confidence: 83%
“…52 Although it is assumed that it is the early-life farm contact that confers a protective effect against allergic diseases, new data show that regular farm animal contact starting later in life is also associated with a decreased prevalence of sensitisation among adults. 53 Two small longitudinal studies among young adults 54 and schoolchildren 55 suggest that farm animal contact starting at a later age not only reduces the incidence, but is also associated with a more frequent loss of sensitisation. The study among 42 Austrian agricultural students 54 showed a remission of allergic disease among those with new contact to farm animals; the study, however, was hampered by a high loss to follow up.…”
Section: Endotoxins and Respiratory Health; Results From Environmentamentioning
confidence: 99%
“…53 Two small longitudinal studies among young adults 54 and schoolchildren 55 suggest that farm animal contact starting at a later age not only reduces the incidence, but is also associated with a more frequent loss of sensitisation. The study among 42 Austrian agricultural students 54 showed a remission of allergic disease among those with new contact to farm animals; the study, however, was hampered by a high loss to follow up. The other study 55 was a three year follow up of 844 Austrian schoolchildren (mean age at baseline 8 years).…”
Section: Endotoxins and Respiratory Health; Results From Environmentamentioning
confidence: 99%
“…Prior et al 9 showed a slight overall decrease in FVC over a 4-year follow-up period in a group of 42 young farmers. A larger population-based study showed that after 9 years of follow-up, young individuals exposed to dusts, gases and fumes in different occupations (including farming) did not have a steeper overall decline in lung function than individuals without occupational exposure 10.…”
Section: Introductionmentioning
confidence: 94%